Evaluasi Kebijakan Pembangunan Manusia (IPM) Kabupaten Pemalang Pada Periode 2006-2010 - Agnes Riski Akmalia; Muhammad Adnan; Ahmad Taufiq (Journal of Politic and Government Studies, 2014)
This study was conducted to explain the results of the evaluation of Human Development Index (HDI) in Pemalang. Human Development Index is one measure of UNDP to determine the progress of development in an area especially of human development. The indicators for measuring the Human Development Index is the life expectancy index, education index and the income index. In Pemalang, the achievement that gained was 69.89% in 2010 with a ranking of 34 from all district / city in Central Java. When compared with Pekalongan District in ranking 23 and Tegal District in ranking 8, Pemalang very far behind. So the question is why the Human Development Index in Pemalang low? What the programs of increasing the Human Development Index was according to the target? Human Resources was available? Was the amount of budget also supporting?In order to explain the evaluation of Human Development Index in Pemalang, then used the evaluation method and descriptive analysis with using a quantitative approach. Where the source data obtained from secondary data sources. The coverage of analysis through a qualitative approach that aimed to relevant agencies namely Education, Health, Labor and Transmigration, Bappeda, public hospital, Economy, Doctors, Midwives and School principal.The results showed that when viewed from criteria of the Dunn evaluation, improvement programs of Human Development Index has been fairly good. Although in terms of funds allocated is also still an obstacle due to the increasing needs of the community. The low rankingof Pemalang also not free from the causes therein, the awareness factor of the community in accessing services from the government and the lack of investment development in Pemalang district. Moreover, with substantial funds in education sector reached 58%, medical of 13% and purchasing power of 7%. It showed that Pemalang District was seriously in the increase of Human Development Index. Although ranking that obtained still ranking of 34 but each year the percentage of Human Development Index showed an increasing of 67.4% in 2006 to 69.89% in 2010. This is also evidenced by the superiority of several indicators with Tegal district in education and health sector.Recommendations for this study are to develop an active standby village, improving healthcare, optimizing procurement scholarship, Packet, infrastructure and economic development, increasing local investment, and all that.